(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: to raise the intestinal pattern and control measures adopted by adult individuals with spinal cord trauma. Method: exploratory descriptive study with quantitative approach. Sample of 14 adults with spinal cord trauma. The data collection was done through an interview in the domiciles of the participants. Results: predominance of men; the automobile accident was the main etiology of traumas. Most individuals demonstrated independence for intestinal self-care and the most frequent practices were digitrectal stimulation, abdominal massage and manual extraction of faeces. 92.9% of the individuals attended or had already attended the Specialized Center in Rehabilitation. Conclusions: nursing exercises an important role in the teaching of patient and family selfcare, so it needs skills and knowledge that allow the planning of actions for teaching the care of intestinal disorders, with appropriate interventions aimed at preventing potential complications and improving quality of life of these individuals.